Circuit performance sensitivity analysis of CMOS voltage controlled oscillators - Yang, Jill Ai Hua (2008)
The design of fully-integrated CMOS Voltage Controlled Oscillators, VCO is simulated and compared, together with the study of key device, process and circuit parameters of voltage control oscillators.